Pensée design et Facebook. Un accompagnement prometteur de citoyennes dans la réduction des plastiques au Maroc - Diane Pruneau; Abdellatif Khattabi; Zakia Rahmani; Zineb Chattou; Natacha Louis (VertigO)
The over-consmption of plastics in our daily lives results in the generation of significant amounts of solid waste that pose a threat to the environment and human health. Effective solutions to the damage cause by this material would be to reduce the quantities used, reuse or recycle it. To locally reduce the uses, releases and impacts of plastics, two problem-solving tools have been used to support craftswomen in designing solutions to this problem: design thinking and two information and communication technologies (ICT). Design thinking, a human-centered approach to innovation, makes it possible to design solutions by taking into account the needs of users and multiplying prototypes in order to adequately meet these needs. ICTs can help achieve results that would have been unthinkable just ten years ago in terms of scale, speed, quality, accuracy and cost. As part of the “Plastic-free Springs” project, design thinking on Facebook/WhatsApp, groups were used to accompany craftswomen in finding solutions to reduce plastics in the Al Hoceima National Park in Morocco. The research component of the project, which aimed to assess the impact of design thinking on the participants’ learning, allowed to observe changes in their practices, revealing five levels of involvement in the experience according to the taxonomic model of Steinaker and Bell (1979), that is, exposure, participation, identification, internalization and dissemination.